The Potential Risks for the Ecological and Social Security in the Danube Region and their Overcoming in the Context of the New European Agenda - Koev, Krasimir; Popova, Ana (Journal of Danubian Studies and Research, 2023)
Objectives: The aim of this paper is to interpret some risks for the ecological and social security in the Danube region, such us: risks of fire in the forest areas, risks of floods, risks for the natural and cultural heritage, risk of economic and social disproportions in the cross-border areas, etc. Another aim of the study is to discuss the possible solution of risk coping within the frames of the new European agenda for the green transition and carbon-free economies. Prior Work: Theoretical and experimental research of the authors in the field. Approach: Secondary data analysis and overview of cross-border projects and their results focused on the risk overcoming in the Bulgarian-Romanian cross-border region along the Danube river. Results: There is sufficient European funding (Interreg VA Romania-Bulgaria program, Interreg Danube program, Horizon Europe), providing favourable conditions for risk overcoming in the Danube region. It is necessary to increase the capacity of the human resources in the region (public administrations, businesses, NGOs), to elaborate common strategic documents for the cross-border regions and to use the research and innovation potential of the universities within the region in benefit of the economic and social prosperity. Implications: The paper can stimulate a larger discussion in the scientific circles about the necessity of joint research on the new risks and their overcoming. Value: The study will contribute to the interdisciplinary interpretation of the risks in the contemporary societies and will outline the value of the cross-border projects with European funding for risk prevention and management.